PENETAPAN PARAMETER STANDARISASI NON SPESIFIK EKSTRAK BATANG SEREH (Cymbopogon Citrus) - Nawafila Februyani; Muhimmatul Khoiriyah (LPSDI Bina Patria, 2023)
Background: The quality of herbal medicinal products is determined by the quality of the raw materials used. Citronella stem extract (Cymbopogon Citrus) as one of the main raw materials in herbal products, it is necessary to determine non-specific parameters as a step to improve product quality. Objective: to determine non-specific parameters of citronella stem extract. Methods: Non-experimental research design. Lemongrass stem extract was prepared by maceration method using 60% ethanol to obtain a thick extract. Non-specific parameter tests for water content using the toluene distillation method, total ash content and acid insoluble ash content using the gravimetric method, determining the limits for lead (Pb) and cadmium (Cd) metals using Atomic Absorption Spectrophotometry (AAS), as well as microbial contamination including Plate Number Total (ALT) and identification of pathogenic microbes. The results of the study: determination of non-specific parameters of citronella stem extract showed drying losses (%) 23.17, water content (%) 2.43, ash content (%) 3.85, acid insoluble ash content (%) 0.47 , limit for lead (Pb) 0.39 ppm, limit for cadmium (Cd) 0.05 ppm, microbial contamination (CFU/g) > 10, and no colonies of pathogenic microbes E. coli, Salmonella and S. aureus were found. Conclusion: Lemongrass stem extract meets the general requirements based on General Standard Parameters of Medicinal Plant Extracts